Ultrashort imaging to reperfusion time interval arrests core expansion in endovascular therapy for acute ischemic stroke. (3rd November 2012) - Almekhlafi, Mohammed A; Eesa, Muneer; Menon, Bijoy K; Demchuk, Andrew M; Goyal, Mayank
Abstract : Background and purpose: The shorter the time interval between the estimation of the ischemic core by imaging and reperfusion, the more likely that core expansion is minimized. We aimed to assess the feasibility of achieving an ultrashort imaging to reperfusion time in routine clinical practice. Methods The study subjects were a prospective cohort of patients with acute ischemic stroke treated with endovascular therapy in a tertiary center in whom an imaging to reperfusion time of <60 min was achieved. Results: Imaging to reperfusion time of <60 min was accomplished in 11 patients. The median baseline National Institutes of Health Stroke Scale (NIHSS) score was 11 and the median baseline Alberta Stroke Program Early CT Score (ASPECTS) was 8. The median time interval from imaging to endovascular reperfusion was 47 min. The median ASPECTS score on the 24 h CT scan was also 8 and the median 24 h NIHSS score was 1. Upon discharge, 82% of patients achieved a modified Rankin scale score of ≤1. Conclusions: An imaging to endovascular reperfusion time of <60 min is feasible and resulted in minimal core expansion on follow-up imaging in patients with acute ischemic stroke.